PENINGKATAN LITERASI DIGITAL BAGI GURU MADRASAH ALIYAH MELALUI PELATIHAN MICROSOFT EXCEL - Yusuf Nugroho Doyo Yekti; Agus Kusnayat; Aji Pamoso (PT. Jurnal Center Indonesia Publisher, 2024)
This training aims to equip teachers with the ability to prevent data processing errors with Ms Excel. The effectiveness of this training was measured by the one-group pre-test and post-test design method. We used the t-test to find out the difference between pre-test and post-test scores. The results showed a significant difference between the pre-test and post-test scores (p < 0.05). The results showed the average post-test score (mean = 7.60; SD = 1.02) increased almost twice as much as the pre-test average score (mean = 4.58; SD = 1.26). The implications of this training can be applied by teachers to process data, for example, student scores into tables or graphs, so errors are easier to detect. This information can be used to determine decisions, for example, whether a student passes a course or not.